Pengelompokan Fuzzy Pengelompokan Pelanggan Pusat Perbelanjaan Menggunakan Algoritma Fuzzy C-Means - Depriansyah, Yebi; Ardiansyah, M. Febri; Mezi; Rinaldi, M. Kevin (Universitas Bengkulu, 2024)
Customer segmentation is a crucial strategy for understanding consumer behavior and improving marketing efforts. This research aims to classify mall customers based on demographic data and shopping behavior using the Fuzzy C-Means (FCM) algorithm. The dataset employed is the